INNOVATING EDUCATION: PROJECT-BASED TEACHING IN CONCRETE STRUCTURE COURSES - Xiaoming, Wang (Top Educational Review Journal (TERJ), 2023)
Project-based teaching is an innovative pedagogical approach that immerses students in practical projects to enhance their knowledge and skills. This method offers diverse project options tailored to the specific course requirements, such as architectural design, translation projects, and more, to optimize the learning outcomes. This paper illustrates the effectiveness of project-based teaching through architectural design projects. By engaging students in hands-on design and construction tasks in real building projects, they gain in-depth knowledge and practical skills in concrete structure development. Additionally, students have the opportunity to explore and tackle real-world challenges, promoting active and experiential learning